Effectiveness of electric toothbrush as vibration method on orthodontic tooth movement: a split-mouth study - Muhammad Azeem; Ambreen Afzal; Saqib Ali Jawa; Arfan Ul Haq; Mahwish Khan; Husnain Akram (Dental Press Editora, 2019)
Abstract Objective: To investigate the effects of application of vibratory stimuli, using an electric toothbrush, on the rate of orthodontic tooth movement during maxillary canine retraction. Methods: A split-mouth study was conducted in 28 subjects (mean age = 20.8 years; ranging from 18 to 24 years) whose bilateral maxillary first premolars were extracted with subsequent canine retraction. On the Vibration side, light force (100 g) was applied to the canine for 90 days, in combination with vibratory stimuli provided by an electric toothbrush; only orthodontic force was applied to the canine on the non-vibration side. Amount of canine movement was measured monthly. Related to electronic toothbrush usage, a diary was provided to each patient for recording discomfort during experimental period, having 100-mm visual analogue scale (VAS). The paired t-test was used to assess the differences in amount of tooth movement between canines of the vibration and non-vibration sides. Results: The amount of tooth movement was similar for canines on the vibration side and on the non-vibration side (mean 0.81 ± 0.10 mm and 0.82 ± 0.11 mm, respectively, p> 0.05). Plaque accumulation was minimal in any subject throughout the study. No subject reported discomfort as a result of using the electric toothbrush. Conclusions: This study demonstrates that application of vibratory stimuli using an electric toothbrush, in combination with light orthodontic force, do not accelerate orthodontic tooth movement.